Fashion is Spinach, but style is politics: Elizabeth Hawes's functionalist feminism. Issue 1 (4th May 2018) - Cornish, Sarah E.
ABSTRACT: This essay examines three books written by Elizabeth Hawes (1903–1971), better remembered as a fashion designer, claiming that her writing documents a slice of progressive, activist, feminist history of value to feminist modernist and intermodernist studies. The essay introduces Hawes with a brief history of her brand and company, Hawes, Inc., but primarily illustrates the way in which her design career and later involvement with union organizing during World War II informs her critical position in Fashion Is Spinach (1938), Why Is a Dress? Who? What? When? Where? (1941), and Why Women Cry: Wenches with Wrenches (1943). The essay argues that the first two books politicize and de-trivialize dressmaking by developing a functionalist esthetics rooted in a Hawesian definition of "style" and inspired by modern architecture. The essay then analyzes Hawes's socialist and intersectional feminism as it emerges through the wartime union activism she documents in Why Women Cry . I argue overall that the book extends her functionalist philosophy of building a stylish, timeless dress that offers comfort and freedom of movement into a feminist treatise about reorganizing communities for the health, education, equality, and strength of "every human being of every color, race and creed."